Assistive Technologies in Dementia Care: An Updated Analysis of the Literature - Pappadà, Alessandro; Chattat, Rabih; Chirico, Ilaria; Valente, Marco; Ottoboni, Giovanni (Frontiers in Psychology, 2021)
Objectives: Technologies can assist and support both people with dementia (PWD) and caregivers. Recently, the technologies have begun to embed remote components. Timely with the pandemic, the present work reviews the most recent literature on technology in dementia contexts, together with the newest studies about technological support published until October 2020. The final aim is to provide a synthesis of the timeliest evidence upon which clinical and non-clinical decision-makers can rely on choices about technology in the case of further pandemic waves. Methods: A review of reviews was performed alongside a review of the studies run during the first pandemic wave. PsycInfo, CINAHL, and PubMed-online were the databases inspected for relevant papers published from January 2010. Results: The search identified 420 articles, 30 of which were reviews, and 9 were new studies meeting the inclusion criteria. Studies were first sorted according to the target population, then summarised thematically in a narrative synthesis. The studies targeting technologies for PwD were categorised as following: monitoring and security purposes, daily life-sustaining and therapeutic interventions. Each category showed potential benefits. Differently, the interventions for caregivers were classified as informative, psycho-education programs, psychosocial-supportive, therapeutic, cognitive/physical training. Benefits in mental health, skills learning, and social aspects emerged. Conclusions: The evidence shows that technology is well accepted and can support PwD and caregivers to bypass physical and environmental problems, either in regular times or during the next pandemic waves. Nevertheless, the lack of a common methodological background emerges from the analysis. Further and more standardised research is necessary to improve the implementation of technologies in everyday life while respecting the necessary personalisation.